Light Availability for Phytoplankton Production in Turbid Tropical Fish Ponds - Md Yusof, Fatimah (1989)
Primary productivity of green water was determined at different depths using light-dark bottle technique in turbid fish ponds during raining season (May, November and December 1986). The 1% light zone was less than 0.75 m when attenuation coefficients were more than 5. Productivity at various depths was significantly different at intervals of 0.25 m when light attenuation coefficients ranged between 5.09 to 8.39, and at depth intervals of 0.50 m when attenuation coifficients ranged between 3.74 to 4.47. Productivity did not differ significantly when attenuation coefficient was 1.67.